Comparison of Micro-Effects of Vacuum Pumping and Displacement Saturation in Tight Sandstone Cores - Wen, Xin; Li, Xiaomeng (Scientific Journal of Technology, 2026)
As global conventional oil and gas resources dwindle, unconventional resources have emerged as a crucial strategy for China's energy transition and reserve augmentation. Tight sandstone reservoirs, a type of unconventional formation, typically feature complex geology, varied and dynamic structures, and limited inter-pore connectivity, often resulting in low extraction efficiency. To enhance recovery rates from tight sandstone reservoirs, detailed studies of the reservoir's micro-pores are essential. Among these, quantitative evaluation of core micro-pores through laboratory experiments stands as an effective and precise technique. The method of saturating the core is critical in these experiments. Several saturation methods are employed both domestically and internationally, with the most common in the lab being the vacuum and displacement saturation methods. However, a microscopic analysis of the differences between these two methods is lacking. Consequently, this study uses cores from the Chang 7 reservoir in the Ordos Basin to experiment with two saturation methods, leveraging nuclear magnetic resonance (NMR) technology to assess the merits of each through NMR T2 spectrum curves. The findings reveal that for tight sandstone, displacement saturation outperforms vacuum saturation when the relaxation time is less than 0.8ms; for 0.8ms